Hybrid Graphene Ribbon/Carbon Electrodes for High‐Performance Energy Storage. Issue 35 (23rd October 2018) - Farquhar, Anna K.; Supur, Mustafa; Smith, Scott R.; Van Dyck, Colin; McCreery, Richard L.
Abstract: The utility of supercapacitors for both fixed and portable energy storage would be greatly enhanced if their energy density could be increased while maintaining their high power density, fast charging time, and low cost. This study describes a simple, solution‐phase, scalable modification of carbon materials by a covalently bonded "brush" of hydrogen‐terminated graphene ribbons (GRs) with layer thicknesses of 2–20 nm, resulting in a 20–100 times increase in the areal capacitance of the unmodified electrode surface. On a flat sp 2 carbon surface modified by GRs, the capacitance exceeds 1200 µF cm −2 in 0.1m H2 SO4 due to a distinct type of pseudocapacitance during constant current charge/discharge cycling. Modification of high surface area carbon black electrodes with GRs yields capacitances of 950–1890 F g −1, power densities >40 W g −1, and minimal change in capacitance during 1500 charge/discharge cycles at 20 A g −1 . A capacitance of 1890 F g −1 affords an energy density of 318 Wh kg −1 operating at 1.1 V and 590 Wh kg −1 at 1.5 V. The projected energy density of a hybrid GR/carbon supercapacitor greatly exceeds the current 10 Wh kg −1 for commercial supercapacitors and approaches that of lithium ion batteries. Abstract : Graphene ribbons are formed on flat or high surface area carbon electrodes by a solution process. The increased microscopic surface area in combination with a significant faradaic component results in areal capacitance exceeding 1200 µF cm −2 and gravimetric capacitance exceeding 1800 F g −1 .